2014
DOI: 10.1002/hep.27048
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete hepatitis B immunization, maternal carrier status, and increased risk of liver diseases: A 20-year cohort study of 3.8 million vaccinees

Abstract: Hepatitis B immunization has been documented to prevent fulminant hepatic failure (FHF) and hepatocellular carcinoma (HCC) by historical comparison studies in Taiwan. This study aimed to assess long-term risks and predictors of various liver diseases associated with incomplete immunization in 3.8 million vaccinees. Profiles of the National Hepatitis B Immunization Registry, National Cancer Registry, and National Death Certification Registry were linked to ascertain newly diagnosed cases of HCC and deaths from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 34 publications
2
20
0
3
Order By: Relevance
“…The risk of chronic HBV infection, despite HBV birth-dose vaccination, is 3•74 times higher if the interval between the first and second vaccine doses is more than 10 weeks, making adherence to appropriate vaccine schedules essential. 48 A Taiwanese study 49 ; HRs calculated after adjustment for maternal HBsAg status) in those who become infected with HBV. Unfortunately, full vaccine coverage with three HBV vaccine doses is poor: WHO-UNICEF estimated that in 2015, only 77% of infants in Africa received full vaccine coverage.…”
Section: Seriesmentioning
confidence: 99%
“…The risk of chronic HBV infection, despite HBV birth-dose vaccination, is 3•74 times higher if the interval between the first and second vaccine doses is more than 10 weeks, making adherence to appropriate vaccine schedules essential. 48 A Taiwanese study 49 ; HRs calculated after adjustment for maternal HBsAg status) in those who become infected with HBV. Unfortunately, full vaccine coverage with three HBV vaccine doses is poor: WHO-UNICEF estimated that in 2015, only 77% of infants in Africa received full vaccine coverage.…”
Section: Seriesmentioning
confidence: 99%
“…13,14 Chien et al found that incomplete neonatal immunization would cause higher incidence for hepatocellular carcinoma, mortality of fulminant hepatic failure and chronic liver diseases as compared with completely vaccinated newborns. 15 Moreover, application of different types or doses of vaccines may also influence primary antibody responses, development of immune memory and mean anti-HBs levels. [16][17][18] Some studies mentioned about the efficacy of different types of vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, the present study showed a high incidence of HBV infection and a dramatically low level of protection against hepatitis B among young French adults at risk of sexually transmitted diseases. Studies evaluating the impact of mass vaccination campaigns against HBV, in particular from the Taiwanese experience, have shown that such campaigns dramatically reduced HBsAg prevalence and the incidence of feared complications of HBV infection, in particular fulminant hepatitis and hepatocellular carcinoma [26,27]. In Europe, the best vaccination policy is still under debate; the majority of European countries have universal HBV vaccination programmes, whereas six countries prefer targeting high-risk groups [28,29].…”
Section: Discussionmentioning
confidence: 99%